Five-Year Plan for 1956-57 Part I and II Government of Bihar Finance Department - Planning Commission (Planning Commission, 1956)
Award of scholarships, hostel grants, book grant, university examination fees and petty grants to scheduled castes students reading in colleges and schools construction of hill pathways and village roads in tribal areas. Medical schemes—thicker leprosy cure centre—miscellaneous schemes. Grants-in-aid to institutions and individuals working for the welfare of scheduled tribes.
Government of Bihar
Government of Bihar Finance Department
Keywords: Receipts from road transport scheme working expenses; Working expenses. Other revenue expenditure financed from Ordinary revenue; scientific department; miscellaneous departments; expenditure on revenue account; construction of irrigation; navigation; capital outlay on industrial development; Loans And Advances By The-State Government